2019
DOI: 10.1007/s00261-018-1867-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving preoperative detection of synchronous liver metastases in pancreatic cancer with combined contrast-enhanced and diffusion-weighted MRI

Abstract: Purpose To explore the value of gadolinium-enhanced MRI combined with diffusion-weighted MRI (Gd-enhanced MRI with DWI) in addition to contrast-enhanced CT (CECT) for detection of synchronous liver metastases for potentially resectable pancreatic cancer. Methods By means of a retrospective cohort study we included patients with potentially resectable pancreatic cancer on CECT, who underwent Gd-enhanced MRI with DWI between January 2012 and December 2016. A single observer evaluated MRI and CT and was blinded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…Most studies that have been performed for liver metastases of PDAC are retrospective, including our single center study in patients with potentially resectable pancreatic cancer without liver metastases on CECT [25]. In this study Gadolinium (Gd) enhanced MRI with DWI detected synchronous liver metastases in 24% of patients with potentially resectable pancreatic cancer on CECT with a sensitivity of 84%.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Most studies that have been performed for liver metastases of PDAC are retrospective, including our single center study in patients with potentially resectable pancreatic cancer without liver metastases on CECT [25]. In this study Gadolinium (Gd) enhanced MRI with DWI detected synchronous liver metastases in 24% of patients with potentially resectable pancreatic cancer on CECT with a sensitivity of 84%.…”
Section: Introductionmentioning
confidence: 75%
“…The sample size is calculated based on a method for power calculations for diagnostic studies described by Jones et al [30]. Based on literature and our previously performed retrospective study [9,[31][32][33][34][35] we estimate the sensitivity of MRI will be approximately 90%. In literature the specificity for MRI is usually higher than the sensitivity, therefore we based our sample size calculation on the sensitivity only.…”
Section: Sample Sizementioning
confidence: 99%
“…A further advantage of MRI as guidance modality is the high sensitivity in detection of small liver lesions [28]. Several studies have shown that MRI has a higher sensitivity in detection of small liver lesions in comparison to CT, so that preoperative acquisition of hepatic MRI can lead to a significant change in the treatment plan [29]. In four of our study patients, planning imaging at the beginning of the intervention revealed six new and therefore suspicious lesions, which could be successfully treated in the same procedure.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, combinations of CT modalities have improved its efficacy to a large extent. Likewise, combining diffusion-weighted MRI with CE-MRI has nearly doubled the early detection of liver metastasis (from 156 to 397 cases) ( 40 ).…”
Section: Detection Methodsmentioning
confidence: 99%